Novel developments on the association of the AHR-CYP1A1 axis and arterial hypertension related to obstructive sleep apnea - Pimpão, António Manuel Bacalhau (2021)
Chronic intermittent hypoxia (CIH) is responsible for the development of systemic hypertension (HTN) in patients with obstructive sleep apnea (OSA). OSA is a common cause of resistant HTN. CIH promotes AHR activation, particularly in the kidney, with a consequent increase in Cyp1a1 expression. Moreover, using an animal model of CIHHTN, it was demonstrated that the AHR antagonist (CH-223191) might represent a promising anti-hypertensive molecule. This pharmacological effect was only apparent in animals’ active period. However, available information on CH-223191 pharmacological pathways in kidney is scarce, as they are the mechanisms that associate CYP1A1 to blood pressure control. We herein focused on Cyp1a1 in kidney cortex by investigating its circadian variation as well as the gender-differences and the impact of IH chronicity in its expression (Western Blot). Transcriptomic analysis using Next-Gen RNA-Seq and bioinformatics allowed the identification of molecular mechanisms by which CH-223191 acts, both in normoxia- and CIH-exposed animals. The results indicate that the circadian pattern of CYP1A1 is opposite between male and female. For the first time is also described that the impact of IH in Cyp1a1 is dependent on the duration of IH exposure. Indeed, the effect is opposite in short- and long-term exposure: a short-term exposure (not enough to induce HTN) decreases Cyp1a1 expression and a long-term exposure, when HTN is already established, increased Cyp1a1 expression. Moreover, the pharmacological pathways of CH-223191 in kidney cortex were also disclosed. In normoxia, CH-223191 mostly under-expressed genes, but in CIH conditions it mostly over-expressed genes. Some of the identified genes are involved in BP regulation and/or in (dys)metabolic features. This work represents a forward step towards an advance regarding the relevance of the AHR-CYP1A1 axis activation in OSA-HTN, paving the way for innovative drugs for this particular type of HTN, which is difficult to control with the available anti-hypertensive drugs